2017
DOI: 10.1089/pho.2016.4173
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2Laser: From Skin Rejuvenation to Vulvo-Vaginal Reshaping

Abstract: Fractional micro-ablative CO laser seems to reduce symptoms related to vaginal atrophy. The beneficial effects were reported just after the first session and confirmed 12 months after the last session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 18 publications
1
41
0
3
Order By: Relevance
“…Кроме того, некоторым женщинам противопоказана гормональная терапия, или вскоре после лечения у них наблюдается рецидив. В настоящее время отсутствует достаточное количество данных долгосрочных исследований относительно безопасности гормональной терапии и остается без ответа важный вопрос о том, безопасно ли применение местной терапии эстрогенами у пациентов, перенесших рак [13,14].…”
Section: Conflict Of Interestunclassified
“…Кроме того, некоторым женщинам противопоказана гормональная терапия, или вскоре после лечения у них наблюдается рецидив. В настоящее время отсутствует достаточное количество данных долгосрочных исследований относительно безопасности гормональной терапии и остается без ответа важный вопрос о том, безопасно ли применение местной терапии эстрогенами у пациентов, перенесших рак [13,14].…”
Section: Conflict Of Interestunclassified
“…The effect of fractional CO 2 laser on women reporting symptoms of vulvovaginal atrophy (dryness, itching, burning, dyspareunia, discomfort, urinary symptoms) was recently evaluated by Filippini et al 31 in 386 postmenopausal women. In menopause, due to the lack of the estrogenic support to the genital mucosa, vaginal rejuvenation often involves a restoration of the vaginal wall connective tissue and the adequate tissue water content, besides a mere anatomical surgical correction to tighten the vaginal diameter.…”
Section: Vaginal Rejuvenation: Surgical Options Efficacy and Complimentioning
confidence: 99%
“…Decreasing levels of estrogen cause thinning and atrophy, loss of elasticity, and loss of functionality of the vaginal mucosa, leading to dryness, itching, burning, dysuria, and dyspareunia. [34][35][36] AFLs can play a role in stimulating the tissue to restore structure and function. In a large study of 386 patients, 3 treatments with a fractional microablative CO2 laser showed a resolution of the aforementioned symptoms in a majority of patients.…”
Section: Skin Rejuvenation and Skin Tighteningmentioning
confidence: 99%
“…In a large study of 386 patients, 3 treatments with a fractional microablative CO2 laser showed a resolution of the aforementioned symptoms in a majority of patients. 34 Much of the improvement was appreciated even after the first treatment. Histological studies have confirmed a successful remodeling of the vaginal mucosa, with a thickened epithelium with increased glycogen content, as well as increased collagen in the lamina propria.…”
Section: Skin Rejuvenation and Skin Tighteningmentioning
confidence: 99%